2020
DOI: 10.1111/odi.13280
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tooth movement‐induced sclerostin expression using β‐adrenergic receptor blockers

Abstract: Objective Regulation of bone metabolism by the sympathetic nervous system has recently been clarified. Tooth movement is increased by increased bone metabolic turnover due to sympathetic activation. This study aimed to compare the effects of the β‐adrenergic receptor (β‐AR) blockers atenolol (β1‐AR blocker), butoxamine (β2‐AR blocker) and propranolol (non‐selective β‐AR blocker) on tooth movement in spontaneously hypertensive rats (SHR) with sympathicotonia. Materials and Methods Spontaneously hypertensive rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The findings of the study correlate with those reported by Uchibori et al [21] and De Oliveira et al [22], who found that butoxamine (selective beta-2 antagonist) inhibited OTM in rats, due to the inhibition of osteoclasts and RANKL in the pressure zone and the decrease in osteocytes in the tension zone. De Oliveira et al [19] found that propranolol inhibited bone remodeling and OTM en rats due to the reduction of interleukin-1β (IL-1β) and interleukin-6 (IL-6) and a lower expression of the intercellular adhesion molecule-1 (ICAM-1) and RANKL.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the study correlate with those reported by Uchibori et al [21] and De Oliveira et al [22], who found that butoxamine (selective beta-2 antagonist) inhibited OTM in rats, due to the inhibition of osteoclasts and RANKL in the pressure zone and the decrease in osteocytes in the tension zone. De Oliveira et al [19] found that propranolol inhibited bone remodeling and OTM en rats due to the reduction of interleukin-1β (IL-1β) and interleukin-6 (IL-6) and a lower expression of the intercellular adhesion molecule-1 (ICAM-1) and RANKL.…”
Section: Discussionsupporting
confidence: 91%
“…The nerve endings within paradental tissues mainly consist of mechanoreceptors and nociceptors. The use of beta-adrenergic receptor blockers such as atenolol decreased tooth movement, suggesting the regulation of bone metabolism by the sympathetic nervous system 26 . The sympathetic nervous system regulates bone resorption mainly through the β-2 adrenergic receptor (Adrb2), one of the three postsynaptic β adrenergic receptors.…”
Section: Hypothetical Theories and Four Steps For Mechanisms Of Otmmentioning
confidence: 99%
“…The selective β‐blocker metoprolol prevents bone loss in a rat ovariectomy model, ( 44 ) and selective (including β2‐selective) and nonselective β‐blockers prevent tooth movement in spontaneously hypertensive rats. ( 45 ) The highly β1‐selective β‐blocker nebivolol improves fracture healing in rats, but whether this is though a vascular mechanism or by targeting cells involved directly in bone repair is unclear. ( 46 ) None of these studies examined the combination of β‐blockers with PTH.…”
Section: Discussionmentioning
confidence: 99%